1987
DOI: 10.1002/1097-0142(19871115)60:10<2366::aid-cncr2820601003>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine arabinoside/cyclophosphamide pulses during continuation therapy for childhood acute lymphoblastic leukemia. Potential selective effect in T-cell leukemia

Abstract: One hundred seventy-seven children with acute lymphoblastic leukemia (ALL) were admitted to a study designed to determine whether pulses of cytosine arabinoside (ara-C) and cyclophosphamide (cyclo) would improve disease-free survival (DFS). All patients received vincristine, prednisone, and asparaginase for remission induction, CNS prophylaxis with cranial irradiation and intrathecal methotrexate, and continuation therapy with 6-mercaptopurine plus methotrexate. Forty-seven of 101 patients with non-T ALL and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
(2 reference statements)
0
23
0
Order By: Relevance
“…Arabinofuranosylcytosine (Ara-C), the clinically useful antimetabolite of cytidine, is one of the most important antitumor agents, especially used in the treatment of various leukemias and carcinomas of the colon, breast and ovary [51]. Like many inhibitors of DNA synthesis, the therapeutic use of Ara-C is largely hindered by its toxicity to normal dividing cells.…”
Section: -Fumentioning
confidence: 99%
See 1 more Smart Citation
“…Arabinofuranosylcytosine (Ara-C), the clinically useful antimetabolite of cytidine, is one of the most important antitumor agents, especially used in the treatment of various leukemias and carcinomas of the colon, breast and ovary [51]. Like many inhibitors of DNA synthesis, the therapeutic use of Ara-C is largely hindered by its toxicity to normal dividing cells.…”
Section: -Fumentioning
confidence: 99%
“…Moreover, this drug is subject to rapid enzymatic deactivation by cytidine deaminase to arabinofuranosyluridine (Ara-U) [54]. Several modifications have been envisaged in order to minimize such drawbacks [51]. Several modifications have been envisaged in order to minimize such drawbacks [51].…”
Section: -Fumentioning
confidence: 99%
“…This hypothesis was supported by studies in mice which demonstrated that thymic leukaemia was more sensitive to cyclophosphamide and cytarabine than methotrexate and mercaptopurine (Frei et al, 1974). A comparative clinical Months in continuous complete remission Figure 8a Children with non-T lymphoid leukaemia were not benefited by addition of cyclophosphamide and cytarabine to their continuation chemotherapy (Lauer et al, 1987). b, For T-cell lymphoid leukaemia, only children who received cyclophosphamide and cytarabine remained in remission (Lauer et al, 1987).…”
Section: The Limits Of Intensification Of Treatmentmentioning
confidence: 99%
“…However, in mice it was demonstrated that cyclophosphamide and cytarabine were more effective in AKR leukemia, a T-cell line, and Sullivan et al suggested that cytarabine was specifically effective in human T-cell lymphoma/leukemia [42,47]. A comparative study in children with ALL in remission demonstrated that the cure rate of T-cell ALL approached that of non-T ALL when the T-cell patients received cyclophosphamide and cytarabine in addition to methotrexate and mercaptopurine [26]. On the other hand, the cyclophosphamide and cytarabine provided no curative benefit, only additional toxicity, to children with non-T ALL receiving methotrexate and mercaptopurine.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Survival and cure depend on the administration of appropriate drugs in appropriate schedules. For example, when T-cell ALL was 30 treated with conventional non-TALL chemotherapy it had a rapidly fatal course in most patients [26]. Features associated with T-cell ALL such as thymic mass, male sex, high white cell count, and older age were calculated to be "highrisk" or "bad-prognosis" factors.…”
Section: B Selection and Scheduling Chemotherapy By "Prognostic Factmentioning
confidence: 99%